Growth and Yield Performance of Aus Rice Under Agronomic Managements (Bangladesh Agronomy Journal, 2023)
The experiment was conducted at the experimental field of Sher-e-Bangla Agricultural University, Dhaka during the period from March to June, 2018 to study the effects of agronomic managements on growth and yield of Aus rice. The experiment comprised of split –plot design where varieties in the main plots viz., i) BRRI dhan65 (V1) and ii) Nerica (V2) and five agronomic managements in the sub-plots viz., i) No management-M0, ii) No weeding, but all other managements-M1, iii) No fertilizer application, but all other managements-M2, iv) No irrigation application, but all other managements-M3 and v) Recommended management-M4, respectively. Almost all the studied characters were found statistically significant due to variation in treatments. Significant variation was recorded different yield contributing characters and yield of Aus rice. At 30, 50, 70 DAS and harvest, the taller plant (24.61 cm, 41.27 cm, 60.23 cm and 80.28 cm, respectively), grain yield (0.96 t ha-1) and straw yields (2.75 t ha-1) were recorded from V2 compared to that of V1. Similarly, the tallest plant (27.11 cm, 49.66 cm, 71.49 cm and 91.07 cm at 30, 50, 70 DAS and harvest, respectively), grain yield (2.34 t ha-1) and straw yield (5.30 t ha-1) were observed from M4. In respect of interaction, the highest grain yield (2.43 t ha-1) and straw yield (5.31 t ha-1) were observed from V1M4 (BRRI dhan65 with recommended management), while the lowest grain yield (0.12 t ha-1) from V1M0 (BRRI dhan65 with no management) and straw yield (0.85 t ha-1) from V2M0 (Nerica with no management). Irrespective of variety with no management reduced 94-95% grain yield of Aus rice that was 84-89% for no weeding and no fertilizer application.Bangladesh Agron. J. 2022, 25(2): 43-49